Factors Associated with Return to Sport After Anterior Cruciate Ligament Reconstruction: A Focus on Athletes Who Desire Preinjury Level of Sport - Kawanishi, Yusuke; Kobayashi, Makoto; Yasuma, Sanshiro; Fukushima, Hiroaki; Kato, Jiro; Murase, Atsunori; Takenaga, Tetsuya; Yoshida, Masahito; Kuroyanagi, Gen; Kawaguchi, Yohei; Murakami, Hideki; Nozaki, Masahiro (The Journal of Knee Surgery, 2024)
In most previous studies investigating return to preinjury level of sport (RTPS) after anterior cruciate ligament reconstruction (ACLR), whether patients continue aiming for RTPS not only before but also after ACLR was unclear because environmental and social factors were not considered. Herein, we aimed to evaluate factors associated with RTPS among athletes who desired to achieve RTPS even after ACLR, excluding patients who no longer desire this goal owing to environmental and social factors. Ninety-two patients who underwent primary double-bundle ACLR with a minimum 2-year follow-up and desired to achieve RTPS before surgery were retrospectively enrolled. Twelve (13%) patients who no longer desired to achieve RTPS after ACLR owing to environmental and social factors were excluded. Sixty-nine patients were included in the final cohort. At the final follow-up, the patients were split into two groups: those who achieved (R group) or did not achieve (N group) RTPS based on patient self-assessment. The Knee Injury and Osteoarthritis Outcome Score (KOOS) and Lysholm scores were also determined. The anterior tibial translation in the Lachman test and acceleration and external rotational angular velocity (ERAV) in the pivot shift test were measured at the hardware removal operation. Significant differences were observed for preinjury level of sports between the groups (p < 0.05). The rate of RTPS in competitive athletes was lower than that in recreational athletes (20/46: 43% vs. 16/22: 73%; p =.037). Lysholm score, KOOS symptom, pain, and quality of life showed higher values in the R group than in the N group (p < 0.050). Acceleration was significantly lower in the R group than in the N group (p = 0.028). Competitive level of sports is a risk factor for failure to achieve RTPS. The postoperative functional outcomes in the group that achieved RTPS showed more favorable results. These results provide important information to enable the surgeons to consider the appropriate surgical plan for competitive athletes who desire to achieve RTPS after ACLR.
Keywords: return to preinjury sport level; pivot shift test; anterior cruciate ligament; quantitative measurement